The Emerging Role of Protein Phosphorylation as a Critical Regulatory Mechanism Controlling Cellulose Biosynthesis - Jones, Danielle M.; Murray, Christian M.; Ketelaar, KassaDee J.; Thomas, Joseph J.; Villalobos, Jose A.; Wallace, Ian S. (Frontiers in Plant Science, 2016)
Plant cell walls are extracellular matrices that surround plant cells and critically influence basic cellular processes, such as cell division and expansion. Cellulose is a major constituent of plant cell walls, and this paracrystalline polysaccharide is synthesized at the plasma membrane by a large protein complex known as the cellulose synthase complex (CSC). Recent efforts have identified numerous protein components of the CSC, but relatively little is known about regulation of cellulose biosynthesis. Numerous phosphoproteomic surveys have identified phosphorylation events in CSC associated proteins, suggesting that protein phosphorylation may represent an important regulatory control of CSC activity. In this review, we discuss the composition and dynamics of the CSC in vivo, the catalog of CSC phosphorylation sites that have been identified, the function of experimentally examined phosphorylation events, and potential kinases responsible for these phosphorylation events. Additionally, we discuss future directions in cellulose synthase kinase identification and functional analyses of CSC phosphorylation sites.